2022
DOI: 10.3168/jds.2021-21069
|View full text |Cite
|
Sign up to set email alerts
|

First-milking colostrum mineral concentrations and yields: Comparison to second milking and associations with serum mineral concentrations, parity, and yield in multiparous Jersey cows

Abstract: This observational study described first-milking colostrum mineral concentrations and total yields, and evaluated its associations with cow serum mineral concentrations, parity, and first postpartum milking yield in 100 multiparous Jersey cows from a single herd fed a negative dietary cation-anion difference diet prepartum. Additionally, first-and second-milking colostrum mineral concentrations and total yields were compared in a subset of 65 cows. Serum minerals (Ca, P, Mg, Na, K, Zn, Fe, Cu) were assessed be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 55 publications
0
9
0
1
Order By: Relevance
“…However, it has been reported that blood P concentration was lower in multiparous Holstein cows [ 50 , 51 ]. Additionally, P concentration showed no significant correlation between blood and milk, and further discussion is needed to investigate it [ 14 ]. Likewise, K concentration in multiparous buffaloes also exhibited variations compared with primiparous (18.41 g/100 g versus 16.20 g/100 g) ( p = 0.05).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it has been reported that blood P concentration was lower in multiparous Holstein cows [ 50 , 51 ]. Additionally, P concentration showed no significant correlation between blood and milk, and further discussion is needed to investigate it [ 14 ]. Likewise, K concentration in multiparous buffaloes also exhibited variations compared with primiparous (18.41 g/100 g versus 16.20 g/100 g) ( p = 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…The mineral content of mature milk is also related to milk quality and physicochemical indicators [ 12 ]. Although studies have shown changes in the minerals of Holstein cows’ milk [ 13 , 14 ], parity as an influencing factor in buffaloes has not been studied.…”
Section: Introductionmentioning
confidence: 99%
“…This is the main source of nutrition for baby mammals, including humans, before they can digest other types of food [1]. Early lactation milk contains colostrum [2], which carries maternal antibodies to its young and can reduce the risk of many diseases [3]. It contains many other nutrients, including protein and lactose [4], [5].…”
Section: Introductionmentioning
confidence: 99%
“…Processes such as colostrogenesis, milk synthesis, immune activation, or inflammation challenge the homeostatic and homeorhetic mechanisms responsible to maintain blood calcium (Ca) concentration, and may lead to low blood Ca concentration during the peripartum period ( Horst et al, 2020 ; Valldecabres and Silva-del-Río, 2022 ). Low blood Ca concentration postpartum has been associated in epidemiological studies with undesired outcomes such as increased risk of diseases and reproductive inefficiency ( Rodríguez et al, 2017 ; Valldecabres and Silva-del-Río, 2021a ).…”
mentioning
confidence: 99%